Phylogenic diversity analysis of rumen acetogens in adult sheep fed on conventional roughage diet - MALIK, P K; THULASI, A; SOREN, N M; JOSE, L; PRASAD, K S; PRASAD, C S (The Indian Journal of Animal Sciences, 2015)
The study was conducted to screen the Indian sheep for the presence as well as diversity of rumen acetogens. Rumen liquor samples from 3 adult female sheep (Mandya x Rambouillet) was collected through stomach tube. Genomic DNA was isolated and amplified using touchdown PCR protocol for partial formyltetrahydrofolate synthetase (fhs) gene sequence. Bioinformatic analysis of obtained sequences was done to construct phylogenic tree for molecular characterization and diversity analysis. PCR based amplification and further agarose gel electrophoresis revealed the presence of fhs functional gene in sheep rumen confirming the occurrence of acetogens in adult sheep fed on conventional roughage diet. However, we could not amplify the gene acs conserved with acetogens described by Australian workers. From the phylogenic tree it is clear that act1 group is distant from all other clones (act2 - act10) obtained in this study and represent a distinct uncultured acetogens genera. The act3 and act5 clones are also present in different clusters and are distant to act2, act10, act4 and act6 are closer to each other in the phylogenic tree but distant from act1. From the phylogeny tree it is clear that majority of the acetogens in these sheep are different from those acetogens reported elsewhere in the world. Thus, there is an urgent need to screen our livestock for the acetogens species/strains and to culture them for exploring the prospects of their use as alternate H2 sink for methane mitigation from ruminants.